States as Activists. Issue 2 (3rd April 2019) - Buck, Isaac D.
Abstract: Empowered to play a larger role in the delivery and administration of health care, a number of states are attempting to solve the pharmaceutical pricing crisis in creative and varied ways. This essay summarizes three particular states' more activist approaches, including states that have sought to empower their Medicaid programs to limit coverage of certain drugs based on price, attempted to use leverage to impose cost-efficiency requirements, and, in the most dramatic example, relied on new usage of "gouging" laws to bring down the costs of prescription drugs. Although all three approaches have met substantial resistance, they illustrate a new era of state experimentation in an effort to bring down the cost of prescription drugs.